Pengembangan Media Pembelajaran Wayang Angkrok Kardus untuk Meningkatkan Kemampuan Membilang pada Peserta Didik Kelas I SD Gugus Diponegoro Kecamatan Eromoko - Suprihatin Suprihatin; Suharno Suharno; Mukti Amini (Universitas Mathla'ul Anwar Banten, 2022)
Research Purposes: To describe the procedure for developing learning media for wayang angkrok cardboard learning media, to test the effectiveness of the media developed. This research is a development research conducted at the Diponegoro Gugus Elementary School, Eromoko District, Wonogiri Regency. Data were obtained through tests and non-tests, product effectiveness tests using a before-after experimental design and an average difference test or t-test (independent sample t test). The results showed that the wayang angkrok learning media was relevant enough to be tested in small groups and could be continued at the field trial stage. The test of the effectiveness of the before-after experiment showed that the developed wayang angkrok was effectively used in learning mathematics. The mean difference test shows that the variance of the increase in the ability to count students between small groups and large groups is the same. Thus, it can be concluded that there is a significant (significant) difference in learning outcomes before using the wayang angkrok media and after using the angkrok puppet media in learning mathematics